High performance video graphic architecture using hybrid logarithmic system - Rizalafande, Che Ismail, Dr. (Universiti Malaysia Perlis (UniMAP), 2014)
Received a Gold medal in 25th International Invention, Innovation & Technology Exhibition (ITEX'14), 8th-10th May at Kuala Lumpur Convention Centre.